Penerapan Pembelajaran Nahwu di Ma’had Al-Birr Universitas Muhammadiyah Makassar - Eka Mahendra Putra; Lukman Abd. Shamad Dampang; Amran AR; Muhammad Fauzi Anas; Fitrah Mujetaba (Universitas Islam Ahmad Dahlan Sinjai, 2025)
This study aims to analyze the implementation of nahwu (Arabic syntax) learning among students at Ma’had Al-Birr, Muhammadiyah University of Makassar, and to identify the supporting and inhibiting factors in the learning process. This research employed a qualitative approach with a descriptive design to gain an in-depth understanding of the dynamics of nahwu learning within the context of Islamic higher education. Data were collected through in-depth interviews, classroom observations, and documentation involving students and lecturers teaching nahwu. Data analysis was conducted using thematic analysis, supported by source, method, and time triangulation to ensure data validity. The results indicate that nahwu learning is implemented through a combination of interactive lectures, group discussions, Arabic text analysis, and sentence writing practices. These approaches significantly improve students’ ability to understand syntactic structures, read Arabic texts, and write grammatically correct sentences. However, several challenges remain, including differences in students’ prior Arabic proficiency, the complexity of nahwu concepts, limited instructional time, and the underutilization of technology-based learning media. The novelty of this study lies in the identification of an integrative-applicative nahwu learning model that combines traditional pesantren-based approaches with modern participatory learning strategies, thereby addressing both academic demands and the learning characteristics of contemporary students in the digital era